WAP development with WML and WMLScript - Forta, Ben (SAMS, 2000)
This book introduces WML and WAP as wireless application development tools and teaches the reader how to develop WML applications. The reader will learn about mainstream topics such as security over wireless networks, working with image files for handheld displays, and interacting with wireless users. Readers will also learn about some of the more obscure items that could be needed in their use of WML/WAP, such as dealing with a variety of micro-browser hardware and integrating WAP/WML into standard Web server technologies.